Estratégia de produção e produção enxuta: um estudo de caso em uma grande empresa metal-mecânica - Sciuto, Joseleine Maria (2012)
The literature about Production Strategy proposes that the production function should be considered as a strategic asset and as a competitive weapon. The Production Strategy adopted in the company resulting from the implementation of improvement programs, and they may provide advances in targeted competitive dimensions. However, many times and for various reasons, the implemented programs do not generate the expected results. In this work seeks to identify and characterize the Production Strategy of a large metallurgical company and discuss whether there is alignment between improvement programs that have been deployed as part of the Lean Production system and the Competitive Priorities of production as perceived by some of his managers. The survey information for this case study was done through interviews with some managers, analysis of company documents and direct observation at the factory. The discussion on the possible alignment also involved an investigation of compatibility between the actions drivers and improvement projects and set priorities Competitive considered crucial to the organization. The study indicates that improvement programs implemented with the Lean Production system have involved almost exclusively infrastructural decision areas and were not always oriented to the production s Competitive Priorities perceived by managers. Thus, we can not say that the Lean Production system that is being implemented by the company fully meets the Production Strategy that managers want to adopt. Improvements in the relationship between PE and PE could be achieved in the company if the improvement actions drivers were clearly defined in a decision process that counted with the participation of senior management, and the actions and tools implemented would focus Criteria Competitive desired by the organization.